THE CRIMINAL RESPONSIBILITY BY CORPORATE - Dwi Wahyono (International Journal of Law Reconstruction, 2021)
Corporation is the subject of a criminal act. In Indonesia, the statutory regulations that initiated the placement of corporations as subjects of criminal acts and which can be directly accounted for are Act No. 7 the Emergency of 1955 concerning Investigation, Prosecution and Economic Criminal Justice, as subjects of criminal law corporations do not have an inner attitude. Meanwhile, to be criminally accountable, a men's rea/schuld is required. Crimes committed by corporations are very detrimental to society and the state. Meanwhile, the conventional accountability system which is individual, direct, and based on schuld, is difficult to apply to corporations. The purpose of writing is to analyze the corporate liability system to impose crimes against corporations, and obstacles to imposing crimes against corporations. The method used is the statute approach (legal approach) and the case approach (case approach), the analysis method uses qualitative analysis with interpretation, and the data collection method uses library research. It can be concluded that corporations can be held accountable by using a system of absolute and substitute liability, and the obstacle is the application of a conventional criminal liability system and the difficulty of proving corporate wrongdoing. It is suggested that there is a common perception between law enforcers about the criminality of corporations.